PENGARUH LINGKUNGAN KERJA DAN PEMBERIAN MOTIVASI KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT PESISIR HIDRO ENERGI GUNTUNG AGAM SUMATERA BARAT - Zahara "; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to influence the work environment and providing work motivation on employee morale at PT Pesisir Hidro Energi Guntung Agam, West Sumatra. Work Environment Variable as a variable (X1), Providing Work Motivation as a variable (X2) and Employee Morale as a variable (Y). This research method is descriptive quantitative using the SPSS 23 program, where the sample used is 107 employees using a random sample collection technique and data collection using a questionnaire. From the results of data analysis which includes validation test, reliability test, determination test, multiple linear regression, t test, F test so it can be concluded that the work environment partially has a positive and significant effect on employee morale, giving work motivation partially has a positive and significant effect on Employee Morale, Work Environment and Providing Work Motivation simultaneously have a significant effect on Work Morale at PT Pesisir Hidro Energi Guntung. Keywords: Work environment, Giving Work Motivation and Work Morale